The use of perineural catheters in pediatric population - Simić, I.; Simić, D.; Stanković, Z.; Petrov, I.; Stević, M.; Dučić, S. (Pain medicine, 2017)
Perineural catheters (PCs) provide prolonged effect of the peripheral nerve block, and through a percutaneously placed catheter, whose top is near the nerve or nerve plaxus, local anesthetic is titrated to the desired effect. Catheter placement is performed under the control of ultrasound and / or neurostimulator. After placement, tunneling is carried out to ensure the adequate position of the catheter. PCs can be placed on the upper extremities (an extended block of the brachial plexus using an interscalene, supra/infra-clavicular or axillary nerve approach), lower extremities (prolonged lumbosacral plexus block, femoral, ischiadic or popliteal block) and other perineural blocks (thoracic, ilioinguinal, paravertebral, tap etc.) PCs have an increasing implementation on pediatric patients with aim to provide intraoperative anesthesia, postoperative analgesia and chronic pain therapy. Numerous studies on pediatric patients have shown that perineural catheters improve control of postoperative pain and lead to reduced use of opioids, thereby reducing the risk of side effects. The most common use of PCs is in orthopedic surgeries, where they significantly regulate postoperative pain and allow early use of physical therapy, better post-operative recovery, and reduce time of hospitalization. With adequate training of parents, they can be used at home. Due to the small number of contraindications (allergic reaction to local anesthetics, infection on the site of placement, patient refusal), and improvements in clinical, economic and humanistic approach, PCs have an increasingly important application. PCs improve the control of post-operative pain, reduce the use of analgesics and opioids, reduce post-operative complications nausea and vomiting, reduce time spend in hospital, require less treatment costs and improve the satisfaction of children and their parents.